2000
DOI: 10.1073/pnas.140217397
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proteasomal degradation by the Gly-Ala repeat of Epstein–Barr virus is influenced by the length of the repeat and the strength of the degradation signal

Abstract: The Gly-Ala repeat (GAr) of the Epstein-Barr virus nuclear antigen-1 is a transferable element that inhibits in cis ubiquitin͞ proteasome-dependent proteolysis. We have investigated this inhibitory activity by using green fluorescent protein-based reporters that have been targeted for proteolysis by N end rule or ubiquitin-fusion degradation signals, resulting in various degrees of destabilization. Degradation of the green fluorescent protein substrates was inhibited on insertion of a 25-aa GAr, but strongly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 25 publications
9
55
0
Order By: Relevance
“…Using an in vitro processing assay, it was shown that the GAr is a specific inhibitor of ubiquitin-dependent proteolysis and acts as a transferable element that, when expressed in the context of other viral or cellular proteasome substrates, abrogates or severely inhibits their degradation (Levitskaya et al, 1997). Several features of this stabilization signal were revealed using a set of GAr chimeras involving IkB (Sharipo et al, 1998), p53 (Heessen et al, 2002) and green fluorescent protein (GFP)-based proteasome substrates in mammalian (Dantuma et al, 2000a) and budding yeast (Heessen et al, in press). It was found that the activity of the GAr is independent of its location in the target protein (Levitskaya et al, 1997;Sharipo et al, 1998;Dantuma et al, 2000a;Heessen et al, 2002) and is not restricted by the type of ubiquitin ligase involved in substrate modification (Sharipo et al, 1998;Dantuma et al, 2000a;Heessen et al, 2002).…”
Section: The Rescue Program: Lmp-2a and The Capture Of Cellular Ubiqumentioning
confidence: 99%
See 2 more Smart Citations
“…Using an in vitro processing assay, it was shown that the GAr is a specific inhibitor of ubiquitin-dependent proteolysis and acts as a transferable element that, when expressed in the context of other viral or cellular proteasome substrates, abrogates or severely inhibits their degradation (Levitskaya et al, 1997). Several features of this stabilization signal were revealed using a set of GAr chimeras involving IkB (Sharipo et al, 1998), p53 (Heessen et al, 2002) and green fluorescent protein (GFP)-based proteasome substrates in mammalian (Dantuma et al, 2000a) and budding yeast (Heessen et al, in press). It was found that the activity of the GAr is independent of its location in the target protein (Levitskaya et al, 1997;Sharipo et al, 1998;Dantuma et al, 2000a;Heessen et al, 2002) and is not restricted by the type of ubiquitin ligase involved in substrate modification (Sharipo et al, 1998;Dantuma et al, 2000a;Heessen et al, 2002).…”
Section: The Rescue Program: Lmp-2a and The Capture Of Cellular Ubiqumentioning
confidence: 99%
“…Several features of this stabilization signal were revealed using a set of GAr chimeras involving IkB (Sharipo et al, 1998), p53 (Heessen et al, 2002) and green fluorescent protein (GFP)-based proteasome substrates in mammalian (Dantuma et al, 2000a) and budding yeast (Heessen et al, in press). It was found that the activity of the GAr is independent of its location in the target protein (Levitskaya et al, 1997;Sharipo et al, 1998;Dantuma et al, 2000a;Heessen et al, 2002) and is not restricted by the type of ubiquitin ligase involved in substrate modification (Sharipo et al, 1998;Dantuma et al, 2000a;Heessen et al, 2002). Fusions of the GAr to GFP-based reporters that are targeted for degradation with different efficiencies (Dantuma et al, 2000b) showed that the GAr counteracts the degradation signal in a length-dependent manner (Dantuma et al, 2000a).…”
Section: The Rescue Program: Lmp-2a and The Capture Of Cellular Ubiqumentioning
confidence: 99%
See 1 more Smart Citation
“…41 However, the effect of these peptides on antigen presentation was not determined. 42,43 Subsequent studies have shown that cotranslational ubiquitination of EBNA-1 can override the GArmediated inhibition of proteasomal degradation and restore the endogenous processing and presentation of MHC class I-restricted CTL epitopes. 44 This suggests that the GAr domain not only prevents proteasomal degradation but also ubiquitination of GAr domain-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless EBNA1 is a very attractive viral antigen for a therapeutic target due to its ubiquitous presence in all EBV infected cells, and novel strategies to avoid the restricted class I processing of EBNA1 have been reported by several groups. In the experiment of Tellam and his collegues, the EBNA1 gene was covalently linked with ubiquitin, and subject to targeting to the N-end rule pathway, in which the stability level of a protein in vivo can be dramatically changed by the identity of its N-terminal residue (Varshavsky, 1996;Tobery and Siliciano, 1999;Dantuma et al, 2000). These modifi cations dramatically enhanced intracellular degradation of the protein and restored CD8+ T cell recognition, demonstrating that GAr-mediated proteosomal blockade on EBNA1 can be reversed (Tellam et al, 2001).…”
Section: Ebna1mentioning
confidence: 99%